2004
DOI: 10.1002/ajmg.a.20585
|View full text |Cite
|
Sign up to set email alerts
|

Premature ovarian failure and FRAXA premutation: Positive correlation in a Brazilian survey

Abstract: Fragile X syndrome (FRAXA) is the most common form of inherited mental retardation (MR). The mutational mechanism leading to the disease involves an expansion of a trinucleotide repeat located at the 5' UTR region of the gene FMR-1. Four types of alleles can be identified in the population, based on the number of repeats: normal (6-40), gray-zone (41-60), premutated (61-200), and fully mutated (>200). Despite only full mutations being associated with the development of the disorder, some authors propose a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The full mutation results in reduction or complete loss of gene transcription and, therefore, loss of the activity of the protein it encodes, FMRP (Brown 2002;Verkerk et al 1991). The known range of FMR1 CGG repeat expansion-related phenotypes has recently become greater since moderate expansions to a "premutation" range of 50-200 repeats have been found to contribute to premature ovarian failure among female carriers (Hundscheid et al 2000;Machado-Ferreira et al 2004), a tremor/ataxia syndrome among aged male carriers and other neurological phenotypes (Hagerman et al 2001). The neurological premutation phenotypes appear to depend upon the expansion of the mRNA rather than changes in protein structure (Jin et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The full mutation results in reduction or complete loss of gene transcription and, therefore, loss of the activity of the protein it encodes, FMRP (Brown 2002;Verkerk et al 1991). The known range of FMR1 CGG repeat expansion-related phenotypes has recently become greater since moderate expansions to a "premutation" range of 50-200 repeats have been found to contribute to premature ovarian failure among female carriers (Hundscheid et al 2000;Machado-Ferreira et al 2004), a tremor/ataxia syndrome among aged male carriers and other neurological phenotypes (Hagerman et al 2001). The neurological premutation phenotypes appear to depend upon the expansion of the mRNA rather than changes in protein structure (Jin et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…14,31 In our study, we observed premature ovarian failure in 78.5% of the carrier females with premutation (data not shown), a higher percentage than reported previously. 12,13 Because clinical features typical of FRAXA arise because of the full mutation and consequent methylation of the FMR1 5 0 UTR, clinical checklists can be used to effectively screen individuals with full mutation. In affected individuals, no correlation was observed between clinical severity as measured by clinical score and the number of CGG repeats (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, 21% to 33% of female premutation carriers experience premature ovarian failure. [12][13][14] All males with the full mutation are mentally retarded. About half of the females with the full mutation have mental subnormality or some mild phenotypic features of FRAXA.…”
Section: Introductionmentioning
confidence: 99%
“…El número de repeticiones no se relaciona con el retraso mental asociado al síndrome, sino que aumenta el riesgo creciente de IOP en las mujeres portadoras. Debido a la inestabilidad de la repetición sobre la transmisión de los alelos premutados, las mujeres presentan riesgo de tener niños afectados con síndrome de X fr agil 20 .…”
Section: Fibrosis Quísticaunclassified